Pendampingan Pemanfaatan Legalitas NIB UMKM Quin Koi Farm Melalui Sistem Online Single Submission (OSS) di Kelurahan Pakunden - Gideon Setyo Budi Witjaksono; Shelly Muharrafa Hendinie; Adelya Putri Mahardhika; Izah Bana Murtazah; Sheni Nahla Syifani; Via Aldina Auva (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
This research is used to know the importance of business legality, even the challenges and opportunities faced in running a business. This research was conducted from March to June 2023 which is located in Pakunden Village, Sukorejo District, Blitar City by Group 40 KKN-T MBKM Univesity of East Java